Da Cheng Qi Decoction Alleviates Cerulein-Stimulated AR42J Pancreatic Acinar Cell Injury via the JAK2/STAT3 Signaling Pathway. (10th April 2021) - Zhou, Zehua; Chen, Ying; Dong, Wenmin; An, Rui; Liang, Kun; Wang, Xinhong
Abstract : Background . Acute pancreatitis (AP) is a common acute abdomen inflammation, characterized by the dysregulation of digestive enzyme production and secretion. Many studies have shown that Da Cheng Qi Decoction (DCQD) is a secure, effective prescription on AP. In this study, cerulein-stimulated AR42J cells damage model was established to further explore the feasibility and underlying mechanism of DCQD as a potential inhibitor of JAK2/STAT3 pathway for the treatment of AP. Methods . Cell viability of DCQD was measured using a cell counting Kit-8 assay. Pancreatic biochemical markers such as amylase, lipase, and C-reactive protein production were measured by assay kits, respectively. Cytokines (TNF- α, IL-6, IL-10, and IL-1 β ) were assayed by ELISA. Protein location and protein expression were detected by immunofluorescence staining and Western blotting, respectively. Gene expression was assessed by real-time PCR. For mechanistic analysis of the effect of DCQD on JAK2/STAT3 signaling pathway, selective JAK2 inhibitor (Fedratinib) and STAT3 inhibitor (Stattic) as well as STAT3 activator (Garcinone D) were used. Results . DCQD protected cells by regulating cerulein-induced inflammation and reducing the secretion of pancreatic biochemical markers. Moreover, DCQD could not only inhibit the nuclear translocation of p-STAT3, but also decrease the mRNA expression of JAK2 and STAT3 as well as the ratio of p-JAK2/JAK2 and p-STAT3/STAT3 in protein level. Additionally, DCQD could regulate the mRNA and protein expression of JAK2/STAT3 downstream effectors, Bax and Bcl-XL. The activated effect of cerulein on JAK2/STAT3 pathway was also reversed by JAK2 inhibitor Fedratinib or STAT3 inhibitor Stattic. And the overexpression of JAK2/STAT3 pathway, via STAT3 activator Garcinone D, did exert damage on cells, which bore a resemblance to cerulein. Conclusion . The activation of JAK2/STAT3 pathway may play a key role in the pathogenesis of cerulein-stimulated AR42J pancreatic acinar cell injury. DCQD could improve inflammatory cytokines and cell injury, which might be mediated by suppressing the activation of JAK2/STAT3 signaling pathway.